The country doctor [videorecording (DVD)] - Lilti, Thomas, 1976-; Lilti, Thomas, 1976-; Cluzet, François; Denicourt, Marianne, 1966-; Odent, Christophe (Icarus Films Home Video, 2017)
When the only doctor in a rural French community becomes ill, a woman doctor with opposing views on the practice of medicine comes to replace him.